Rapid amelioration of severe manic episodes with right unilateral ultrabrief pulse ECT: a case series of four patients. (February 2017) - Sidorov, Alexey; Mayur, Prashanth
Objective: The aim of this small case series is to describe four cases of severe mania, where ultrabrief pulse electroconvulsive therapy (ECT) was used as a primary mode of treatment. Methods: A retrospective file review was undertaken of four patients identified as having received ultrabrief pulse ECT for severe mania. The outcome measures for treatment efficacy were the Young Mania Rating Scale (YMRS) and Clinical Global Impression (CGI). Results: All the patients showed significant clinical improvement. A comparison of pre- and post-treatment YMRS and CGI scores showed a dramatic decrease in all four cases. However, one patient was shifted to brief pulse ECT due to inadequate response. Conclusions: Ultrabrief pulse ECT may be an effective treatment in cases of severe mania. Due to the very small number of cases in the current case series, no specific conclusions regarding efficacy may be drawn; however, larger, controlled studies would be indicated.